Hospital admissions for traumatic brain injury: an analysis of the epidemiological profile in the state of Maranhão between 2016 and 2020 (Research, Society and Development, 2022)
Introduction: The traumatic brain injury (TBI) is characterized as an important cause of mortality and morbidity, mental and physical disability, in addition to a disease with a great impact on the quality of life of individuals who suffer from this trauma. Objectives: To evaluate the epidemiological profile of hospital admissions for traumatic brain injury in the State of Maranhão between 2016 and 2020. Methodology: This is an exploratory ecological population-based study that will use secondary data on information from the population that is hospitalized with TBI registered in the online Hospital Admission System of the Unified Health System (SIH/SUS), available on the website of DataSUS. Results: The age group from 20 to 39 years of age represented the largest number of cases of hospitalizations for TBI (42.39%); as for the prevalence per 100,000 inhabitants, the highest rates were in the age group of those aged 80 years or more, which showed an increase of 32.19% from 2016 to 2020; in the traumatic injury profile, the highest prevalence corresponds to unspecified TBI's (other intracranial trauma), accounting for 56.49% of hospital admissions; with regard to the geographic distribution of hospital admissions, the highest concentrations were in the microregions of São Luís, followed by Imperatriz. Conclusion: Men of working age are the most affected in Maranhão, in agreement with other surveys in the country. Systematized studies are needed in order to establish more effective public health education policies to reduce TBI prevalence rates.